Epidemiology, molecular classification and WHO grading of ependymoma - Hübner, Jens-Martin; Kool, Marcel; Pfister, Stefan; Pajtler, Kristian Wilfried (The journal of neurosurgical sciences, 2018)
Ependymoma can arise throughout all compartments of the central nervous system with prevalence for intracranial and spinal location in children and adults, respectively. The current histopathology based WHO grading system distinguishes grade I, II ‘classic’, and III ‘anaplastic’ ependymoma. However, analysis of multiple cohorts of intracranial ependymoma demonstrate a wide variance in the utility of the grade II versus grade III distinction as a prognostic marker that may additionally be confounded by the anatomic compartment. Recent (epi)genomic profiling efforts have identified molecularly distinct groups of ependymoma arising from all three anatomic compartments of the central nervous system that outperform the current histopathological classification regarding clinical associations. These advances have led to the cognition that molecular classification should be part of all future clinical trials in ependymoma patients. Clinical management of intracranial ependymomas (WHO Grade II/III) is challenging and molecular classification based risk stratification may help to intensify treatment and surveillance in high-risk patients but to de-escalate therapy in certain patient groups at low risk for recurrence. Finally, experience of neurosurgeons, and other disciplines, as well as intensified co-operation between all stakeholders involved hold promise to finally improve outcome of patients affected with ependymoma.
Published online: September 8, 2017
Gesehen am 08.11.2018